Práticas de controladoria adotadas por Instituições Privadas de Ensino Superior (IPES) estabelecidas na região centro-oeste do Brasil - Manvailer, Ramão Humberto Martins (Universidade do Vale do Rio dos Sinos, 2013)
This study aims to identify the adoption of controlling practices by Private Institutions of Higher Teaching (PIHT) managers in the central-western region of Brazil. Controllership practices addressed in this research were investigated in the literature and expert opinion submitted to this area of expertise for validation. Such practices were used to make a questionnaire with structured variables in Likert scale and submitted to the managers of Private Institutions of Higher Education (PIHT), in the Center-West region of Brazil. The survey with the instrument used to collect the data was sent by e- mail with a link and / or a form to the respondents. It was Identified that the current practice adopted in the PIHT management are capital budgeting, performance evaluation, internal control to safeguard assets, operational budget, investment return analyses and updated value analyses. In order to identify if there is an association between controllership practices according to the IFAC (1998) four stages classification, and the PIHT characteristics, the Fisher test was used. It is observed that internal control practice in the assets protect ion is adopted by 90% of the medium / large PIHT and also by 62% of the PIHT that have a negative economic performance. The practice cost-volume-profit (CVP) analyses is adopted by 62% of PIHT and presents an association with the nonprofit PIHT. The practice target costing is adopted by 53% of the small PIHT. Thus, we realize that there is an association between controlling practices of the second and third stages with the PIHT characteristics, such as, size, economic performance and administrative classification.
Keywords: Controladoria; Práticas de controladoria; Instituições privadas de ensino superior; Região centro-oeste do Brasil; Comptroller; Controllership practices; Private institutions of higher education; Center-western region of Brazil; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis